Happiness of Working Women and Homemakers in Türkiye: The Role of Social Norms and Issues in the Work and Home Domains - Zeynep B. Uğur (Journal of Economy Culture and Society)
In this study, we analyze the happiness levels of working and homemaker women in Türkiye. For this purpose, we utilized individual-level data from the Life Satisfaction Survey (LSS), covering a 19-year period from 2004 to 2022 with over 344,000 observations. Our findings reveal that even after controlling for various background factors, working women report significantly lower happiness levels than homemakers. The study examined the roles of social norms, work-related issues, and home-related issues. Social norms against women are not overwhelmingly prevalent, as nearly 80% of women does not report significant social pressure due to gender. However, gender-related social pressures partly explain the happiness gap between working women and homemakers. Problems in the work domain do not significantly drive this differential in happiness. Instead, issues in the home domain contribute to the happiness disadvantage, particularly in f inancially better-off households. This suggests that while societal norms play a role, the balance between work and home responsibilities, especially in wealthier households, is crucial for understanding lower happiness levels among working women. The findings underscore the importance of addressing home-related challenges to improve the well-being of working women.